Disputes for the formation of the international regime of human rights: the formation of the regime, the recognition of the human right to development and latin american alternatives to development - De Melo, Vitor Furtado (Seven Editora, 2023)
International regimes are composed of principles, norms, rules, and decision-making procedures capable of converging the expectations of international actors on a given theme. According to this understanding, they are intervening variables between basic causatological factors of the international system, such as the interest and power of its actors, and the consequences of these in terms of the behavior of the same actors. The liberal approach to International Relations attaches great importance to regimes, considering that states rationally agree to adhere to them to make the system more predictable; since its dissemination would sustain a pattern of behavior over time and would open more and more room for cooperation. Although it is possible to consider the independence of the United States of America and the French revolution as the beginning of the process of politicization of human rights, this set of prerogatives only became a subject dealt with in the arena of international politics after the end of World War II. At the time, the current international order was in formation under the already clear leadership of the Government of Washington, so the international regime of human rights, which springs from there, creates contours defined by the idea present in the United States. Thus, a modern and Western philosophy, which excels in civil and individual rights, prevailed when the United Nations General Assembly of the Universal Declaration of Human Rights was accepted in 1948, a document considered the inaugural landmark of the current international human rights regime. From the signing of the declaration, the same philosophy was endorsed with universality and international legitimacy According to the liberal paradigms of International Relations, regimes gain a great deal of importance because they allow the balance and stability of the international system. The critical perspectives of the discipline, in turn, see them as an expression of the power dynamics underway at a given time. Thinking in this way, the prevalence of the forged ideary from the United States and Western Europe in the drafting of the 1948 declaration (and, consequently, in the conformation of the entire international human rights regime) can be understood as a mechanism for sustaining a particular hegemonic order of global scale. Thus, the existing disputes in international politics would be reflected in the concept of human rights and in the universalism with which human dignity is characterized; and would have as instruments the model of development and the human right to development thought from it. This work seeks to address how the international human rights regime not only consolidates patterns of behavior on the part of international actors but also mirrors the factic relations of power between them. Moreover, from a critical perspective, the present work shows how the disputes surrounding the construction of the aforementioned regime are, in fact, ways of consolidating or contesting the hegemonic order in force. To this end, it begins with the analysis of the context and discussions present in international relations in the immediate post-Second World War, at a time of bipolarization typical of the Cold War and the beginning of the internationalization of human rights. It takes place in the examination of the world order of the late twentieth century and, in particular, of how it is reflected at the Vienna World Conference on Human Rights in 1993. The work is finalized with discussions about Latin American alternatives to the way universalism and the human right to development were conceived in Vienna in 1993. Such alternatives concern the ownership of rights by nature and Good Living, which, as demonstrated throughout this essay, are capable of challenging the way the international human rights regime is shaped and, ultimately, the hegemonic order itself in force. DOI: https://doi.org/10.56238/devopinterscie-017